Effect of intra-vaginal electric stimulation on bladder compliance in stress urinary incontinence patients: the involvement of autonomic tone - Lau, Hui-Hsuan; Lai, Cheng-Yuan; Hsieh, Ming-Chun; Peng, Hsien-Yu; Chou, Dylan; Su, Tsung-Hsien; Lee, Jie-Jen; Lin, Tzer-Bin (Frontiers in Neuroscience, 2024)
Objective: In addition to the well-established advantage that strengthened pelvic musculature increases urethral resistance of stress urinary incontinence (SUI) patients, intra-vaginal stimulation (iVES) is also shown to improve bladder capacity via the pudendal-hypogastric mechanism in pre-clinical studies. This study investigated, in the clinical scenario, whether iVES also benefits bladder storage of SUI patients by focusing on compliance, a viscoelastic parameter critically defining the bladder's storage function. Moreover, the potential involvement of stimulation-induced neuromodulation in the iVES-modified compliance was investigated by comparing therapeutic outcomes of SUI patients in response to iVES from trans-obturator tape (TOT) surgery, in which a midurethral sling was implanted without electric stimulation. Patients and methods: Urodynamic and viscoelastic data of 21 SUI patients treated with a regiment of a combination of iVES and biofeedback-assisted pelvic floor muscle training (iVES-bPFMT; 20-minute iVES and 20-minute bPFMT sessions, b.i.w., for 3 months. This regiment complied with the Ethics) and 21 SUI patients received a TOT implantation were retrospectively analyzed. Mean compliance (Cm), infused volume (Vinf), and threshold pressure (Pthr) of the pressure-flow/volume investigations were assayed.Results: Compared with the pre-treatment control, iVES-bPFMT consistently and significantly increased Cm (18/21;85%, p=0.017, N=21) and Vinf (16/21;76%, p=0.046; N=21) but decreased Pthr (16/21;76%, p=0.026, N=21). In contrast, TOT did not result in consistent or significant changes in Cm, Vinf, or Pthr (p=0.744, p=0.295, p=0.651, respectively; all N=21).Our results provide viscoelastic and thermodynamic evidence supporting an additional benefit of iVES-bPFMT to bladder storage of SUI patients via modifying bladder compliance that is possibly coming from the potentiated hypogastric tone, which did not occur in TOT-treated SUI patients.